How Can Crosscutting Concepts Organize Formative Assessments across Science Classrooms? Results of a Video Study - Clarissa Deverel-Rico; Erin Marie Furtak; Sanford R. Student; Amy Burkhardt (MDPI AG, 2024)
Ambitious approaches to science teaching feature collaborative learning environments and engage students in rich discourse to make sense of their own and their peers' ideas. Classroom assessment must cohere with and mutually reinforce these kinds of learning experiences. This paper explores how teachers' enactment of formative assessment tasks can support such an ambitious vision of learning. We draw on video data collected through a year-long investigation to explore the ways that co-designing formative assessments linked to a learning progression for modeling energy in systems could help teachers coordinate classroom practices across high school physics, chemistry, and biology. Our analyses show that while there was some alignment of routines within content areas, students had differential opportunities to share and work on their ideas. Though the tasks were constructed for surfacing students' ideas, they were not always facilitated to create space for teachers to take up and work with those ideas. This paper suggests the importance of designing and enacting formative assessment tasks to support ambitious reform efforts, as well as ongoing professional learning to support teachers in using those tasks in ways that will center discourse around students' developing ideas.